ANALISIS KELENGKAPAN ASESMEN MEDIS GAWAT DARURAT DALAM PENERAPAN REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT X KOTA BOGOR - Rahayu, Sri (Jurnal Infokes, 2023)
Initial assessment of patients, whether in outpatient, inpatient, or emergency department, is very important to know what the patient needs to start treatment. The purpose of this study was to determine the completeness of emergency department medical assessments at X Hospital in Bogor City using SIMRS Hinai. This study uses descriptive research methods with a quantitative design, by conducting observations and interviews. The population of this study was e-medrec emergency medical assessment at Hospital X Bogor City conducted on May 19 - June 2, 2023. The sample in this study was 322 e-medrec emergency medical assessments. This research instrument is an observation checklist. The results of the percentage of completeness of emergency medical assessment e-medrec at Hospital X Bogor City were 153 e-medrecs that were completely filled with a percentage of 48%, the highest completeness was in the Patient Identification section with a percentage of 100% and there were still incompleteness in the Important Notes, Authentification, Good Records section as many as 169 e-medrecs with a percentage of 52%. The percentage of completeness of emergency medical assessment e-medrec at Hospital X Bogor City is in accordance with SOAP. It can be concluded that the completeness of emergency medical assessments in the application of electronic medical records at Hospital X Bogor City is not yet effective because there are still high incompleteness of emergency medical assessment e-medrec in the Important Notes, Authentification, Good Notes section as many as 169 with a percentage of 52% and not in accordance with SOAP. This is not in accordance with the Hospital Minimum Service Standards 100%. Keywords: Completeness, Emergency Medical Assessment, Electronic Medical Records.